2010
DOI: 10.1098/rspb.2010.0491
|View full text |Cite
|
Sign up to set email alerts
|

The missing stink: sulphur compounds can mediate a shift between fly and wasp pollination systems

Abstract: The radiation of the angiosperms is often attributed to repeated evolutionary shifts between different pollinators, as this process drives diversification of floral forms and can lead to reproductive isolation. Floral scent is an important functional trait in many pollination systems but has seldom been implicated as a key mechanism in pollinator transitions. In this study, we suggest a role for sulphur compounds in mediating a shift between specialized carrion-fly and pompilid-wasp pollination systems in Euco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 43 publications
3
114
0
1
Order By: Relevance
“…While some flies such as Musca do have trichromatic spectral sensitivities close to those of hymenopteran trichromats [21,80], fly spectral sensitivities can be readily shifted with molecular manipulations to the opsin sequence [81], suggesting different fly species do not possess colour vision that is as conserved as hymenopteran trichromats [21]. In addition, recent work on fly pollination suggests that olfaction is the main cue used by flies to discriminate between flowers, while colour is not an important cue for these pollinators [82]. It is unlikely that flies are the major driver behind the evolution of flower colours for two other main reasons: (i) as far as is currently known from behavioural experiments on flies, their colour perception is relatively rudimentary and is mediated by simple categorical colour discrimination (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some flies such as Musca do have trichromatic spectral sensitivities close to those of hymenopteran trichromats [21,80], fly spectral sensitivities can be readily shifted with molecular manipulations to the opsin sequence [81], suggesting different fly species do not possess colour vision that is as conserved as hymenopteran trichromats [21]. In addition, recent work on fly pollination suggests that olfaction is the main cue used by flies to discriminate between flowers, while colour is not an important cue for these pollinators [82]. It is unlikely that flies are the major driver behind the evolution of flower colours for two other main reasons: (i) as far as is currently known from behavioural experiments on flies, their colour perception is relatively rudimentary and is mediated by simple categorical colour discrimination (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that flies are the major driver behind the evolution of flower colours for two other main reasons: (i) as far as is currently known from behavioural experiments on flies, their colour perception is relatively rudimentary and is mediated by simple categorical colour discrimination (i.e. spectral differences are only perceived as either 'same' or 'different' to a training stimulus, depending on whether they lie inside a limited number of colour categories) [82,83]. Thus, there is currently a paucity of behavioural data on flies to support that these insects do discriminate colour information in a way that would be the major driver of flower evolution; and (ii) while there is evidence that some flies such as hoverflies do exhibit flower constancy [79], colour cues do not appear to be a factor in flower-constant behaviour in flies and these insects choose randomly between morphs varying in colour [79].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Stensmyr et al (2002) obtained high levels of blowfly attraction to odorless second-day inflorescences of Helicodiceros muscivorus (Araceae) in Sardinia by augmenting them with dimethyl mono-, di-, and trisulfides, the volatile compounds responsible for the intense foul odor of first-day inflorescences. Similarly, Shuttleworth and Johnson (2010) demonstrated that the addition of these same compounds to the inflorescences of wasp-pollinated South African species of Eucomis (subfamily Scilloideae, family Asparagaceae) was sufficient to induce a shift to carrion fly pollination. These results, together with investigations of antennal sensitivity and behavioral bioassays (Cossé and Baker 1996;Stensmyr et al 2002), support the hypothesis that a few specific scent compounds are sufficient to attract saprophilous flies in a variety of settings and habitats.…”
Section: Manuscript Received September 2012; Revised Manuscript Receimentioning
confidence: 99%
“…and Matelea spp. or the stapeliads (family Apocynaceae) and Eucomis flowers (family Asparagaceae) of the Old World (Ollerton and Liede 1997;Jü rgens et al 2006;Shuttleworth and Johnson 2010).…”
Section: Studied Speciesmentioning
confidence: 99%
“…Modifications such as the addition of a single volatile to floral bouquets can add novel functions to it, for example changing the attractive or repellent character of floral scent bouquets (Shuttleworth & Johnson 2010;Junker, Gershenzon & Unsicker 2011;Bischoff et al 2015). In addition to innate preferences for specific volatile compounds or bouquets (Schiestl 2010;Schiestl & D€ otterl 2012), attraction to flowers often involves associative learning (Leonard, Dornhaus & Papaj 2012).…”
Section: Introductionmentioning
confidence: 99%